AB0086 PTH Stimulates Cartilage Formation in Low Turnover Patients – a Possible Systemic Anabolic Treatment for OA?. (9th June 2015) - Siebuhr, A.S.; Gudmann, N.S.; Musa, K.; Kehlet, S.; Hansen, G.; Byrjalsen, I.; Andersen, J.; Bihlet, A.; Christiansen, C.; Karsdal, M.A.; Bay-Jensen, A.-C.; Henriksen, K.
Abstract : Background: Parathyroid hormone (PTH) controls serological calcium levels and is important for bone growth regulation. In addition, PTH may have important roles in articular cartilage homeostasis, which a number of in vitro and in vivo studies have indicated. It has been reported that articular cartilage exposed to PTH have both chondroprotective and chondrodestructive outcomes, so it remains unclear whether the direct effect of PTH on articular cartilage is anabolic and merely remodeling. Cartilage diseases such as osteoarthritis could have benefits of a systemic anabolic treatment. This hypothesis may be investigated by biochemical markers of cartilage turnover in clinical settings. Objectives: In this study we investigated if PTH had cartilage anabolic capacities by a measuring the level type II collagen formation by the serological biomarker ProC2. Methods: In an open labeled, randomized, repeat dose parallel group study of teriparatide (20ug SC) in female osteoporosis patients the serological level of ProC2 was assessed. There were 32 controls (mean age 65.8 years and BMI 25.23) and 32 cases (mean age 66.4years and BMI 24.79). ProC2 was quantified in fasting serum at baseline, week 4, 12 and 24. The ProC2 assay uses a monoclonal antibody to quantify the N-terminal fragment QDVRQPG of type II pro-collagen splice variant B. Two-way ANOVA with Bonferroni's multiple comparisons test was used to investigate the difference between the ProC2 levels at the different time points and in the three groups; low, medium or high ProC2 level at baseline. Results: There were no significant difference between the ProC2 level in cases and controls at any time point. When patients were divided at baseline into low, medium and high ProC2 level, cases with low ProC2 at baseline had significantly increased ProC2 levels at week 12 (P=0.031) and 24 (P=0.025). Furthermore, there was a tendency towards increased ProC2 levels already at week 4 in cases with low ProC2 baseline, though not significant. This relationship was not found in any of the other groups, either cases or controls. In addition, the ProC2 level was significantly increased in the cases with low ProC2 at baseline at week 12 compared to cases with higher ProC2 levels at baseline (P=0.035 and P=0.009). Conclusions: Patients with low ProC2 level at baseline have significantly anabolic effects of PTH after 12 and 24 weeks of treatment. Patients with middle or high levels of ProC2 at baseline do not have anabolic effects of PTH at any time point. This indicates that a sub-population of patient will have anabolic effects of PTH treatment. However, this study cannot identify if the effect of PTH is purely anabolic or merely remodeling, as this study investigated formation of type II collagen and not collagen type II turnover. This means that PTH could be a systemic anabolic treatment for diseases such as osteoarthritis. Disclosure of Interest: None declared